2017
DOI: 10.1016/j.ijheatmasstransfer.2017.04.118
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection heat transfer of turbulent flow in a three-dimensional lid-driven cavity with a rotating cylinder

Abstract: A numerical study has been carried out to investigate the combined forced and natural convection heat transfer in a differentially heated 3D obstructed cavity with a thermally insulated rotating circular cylinder. The cavity has a hot stationary bottom wall and a cold top lid-driven wall, and all the other walls completing the domain are motionless and adiabatic. The simulations are performed for different Reynolds numbers, Re = 5000, 10000, 15000 and 30000, and for dimensionless rotational speeds of the cylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…where C 1ε , C 2ε and C 3ε are model constants and Sk and Sε refer to the user-defined source terms. The remaining terms are written in equations (6)(7)(8).…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…where C 1ε , C 2ε and C 3ε are model constants and Sk and Sε refer to the user-defined source terms. The remaining terms are written in equations (6)(7)(8).…”
Section: Nomenclaturementioning
confidence: 99%
“…The mixed convective flow of moving wall cavity is produced as a result of both natural and forced convection. Since heat convection can be represented in many cavity configurations it has many industrial and engineering applications such as electronic cooling, lubrication technologies, oil extraction, solar collectors, food processing [1][2][3][4][5][6][7][8], many researchers have investigated various free or mixed convection problems. Involving some additional passive objects within the enclosure to enhance the heat transfer ratio has become popular over the years.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated an improvement in the characteristics heat transfer with increasing the baffle height. Kareem and Gao [15] investigated numerically the combined forced and natural convection heat transfer in differentially heated three dimension obstructed cavity with a thermally insulated rotating circular cylinder Reynolds numbers were varied from (5000-30000). Norhaliza et al, [16] presented a numeric analysis with the existence of magnetic field for heat transfer in rectangular enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they found that the highest heat transfer rate occurs for the case with the highest Pr and the smallest aspect ratio. Mixed convection of heat transfer in a lid-driven trapezoidal cavity was studied to find the influence of a combination of different nano-particles and water on the heat transfer rate by Kareem and Gao [27]. Four types of nanofluid were studied for different rotational angle and Reynolds number.…”
Section: Introductionmentioning
confidence: 99%